NATIONAL STUDY OF EMERGENCY DEPARTMENT VISITS AND FOLLOW-UP TREATMENT FOR ATTEMPTED SUICIDE IN OLDER ADULTS. (16th November 2018) - Schmutte, T; Xie, M; O'Connell, M; Marcus, S
Abstract: Little information is available about the mental health care received by U.S. older adults after suicide attempts. This retrospective cohort analysis examined 2015 Medicare claims for adults aged 65 years and older who presented to emergency departments (ED) for self-harm (N=15, 891). Adjusted risk ratios (ARR) were estimated for discharge disposition, ED recognition of mental disorder, and 30-day follow-up mental health outpatient visits. Most patients (76.8%) were hospitalized. Lower likelihoods of hospitalization were observed for African American patients (ARR=0.84, p<.0001), recent medical ED users (ARR=0.92, p=.001), and patients with only one medical comorbidity (ARR=0.91, p=.001). Hospitalization was associated with recent depression (ARR=1.09, p=.004) and recent psychiatric inpatient care (ARR=1.12, p=.003). Among patients discharged to the community (n=3, 681), 48.4% received a mental disorder diagnosis. ED recognition of a mental disorder was associated with age 65–69 years (ARR=1.54, p<.0001) and 70–74 years (ARR=1.23, p=.0004), any recent mental disorder (ARR=1.55, p=.008), and recent mental health care in ED (ARR=1.59, p<.0001), inpatient (ARR=1.32, p=.001), and outpatient (ARR=1.49, p<.0001) settings but inversely related to male sex (ARR=0.89, p=.002) and high lethality self-harm methods (ARR=0.80, p=.001). Only 9.6% of community discharged patients received follow-up outpatient mental health care within 30 days, which was most strongly predicted by prior outpatient mental health care (ARR=6.67, p<.0001). Most older adult Medicare beneficiaries who present to EDs with self-harm are hospitalized. Of those who are discharged to the community, a substantial proportion are not diagnosed with mental disorder in the ED or receive timely follow-up mental health care.